Implementing Programme Student Community Service in Kalinyamat Wetan Village - Arum, Diajeng Putri Sekar (Universitas Pancasakti Tegal, 2022)
Based on the observation and implementation of KKN Daya Sakti Universitas Pancasakti Tegal, which began on July 22, 2019, until September 5, 2019. We can conclude some of the problems faced in Kalinyamat Village Wetan Tegal South Tegal City, namely the lack of child concern for independent learning outside of school, especially elementary school children. The unavailability of a tutoring educational institution becomes one concrete evidence of the absence of reference of the surrounding community or educators to provide independent learning that can offer more insight beyond school hours or lesson hours. The problem is the less equitable economy of the residents of Kalinyamat Wetan Village. In general, the economy of Kalinyamat Wetan residents is quite good. Still, some poor people in Kalinyamat Wetan need capital assistance and skills courses for entrepreneurship. The problem of lack of knowledge about innovations in the field of industry. The level of education is still relatively low in Kalinyamat Wetan, which leads to a lack of information and learning about the latest innovations to developments in the industrial field